(untitled) (Research, Society and Development, 2022)
The present work analyzed aspects related to student learning during the experimental physics disciplines offered during the period of the Exceptional Treatment Regime (RTE) at the Federal University of Itajubá (UNIFEI) in the remote teaching format. The research period comprised the semesters of 2020.2 and 2021.1, being carried out through a Google Forms questionnaire with students regularly enrolled in UNIFEI courses. Students from undergraduate Physics, Bachelor of Physics, and Civil Engineering courses participated in the research. The questions were diversified in order to contemplate quantitative and qualitative aspects of the topic addressed. To support the theoretical framework, articles were used with a focus on science teaching. In the results of this research, alternatives for carrying out experimental activities in the remote format and the main problems that hinder students’ learning are pointed out.